Association Between Individual Differences in Dichotomous Thinking and Current and Childhood High-Crime Environments - Takahiro Mieda; Shinya Yoshino; Atsushi Oshio (Evolutionary Psychology, 2023)
The way people perceive the things around them is closely related to living in a complex and challenging social environment. Dichotomous thinking (preference for dichotomy, dichotomous belief, and profit-and-loss thinking), which classifies things in a simple way, can be useful in dangerous and resource-limited environments. However, based on prior studies, people's manner of perceiving things may have developed as a response to the harshness of their childhood environment, and may not be related to their current environment. Therefore, we examined the relationship between individual differences in dichotomous thinking and high-crime environments as indicators of environmental harshness. We assessed dichotomous thinking in 41,284 Japanese residents using large-scale data from the Human Information Database FY19 compiled by NTT DATA Institute of Management Consulting, Inc. The fixed effects regression model showed that, after controlling for age, high-crime environment of the residents’ childhood was associated with dichotomous thinking, with the exception of dichotomous belief. On the other hand, their current environment of crime was not associated. In sum, our research suggests that people's dichotomous thinking tendency may be a form of adaptation to the harshness of their childhood environment rather than their current one.